The Use of Scramble Game in Improving Students’ Grammar Achievement - Mustaqimah Muh. Tang; A. Nurkidam (LETS: Journal of Linguistics and English Teaching Studies, 2022)
Grammar has been a problem for the EFL learners around the world. It encourages researcher to conduct this research. This action research project aims to see the students’ grammar achievement by using scramble game. The design of this research was Classroom Action Research. This research ran the four steps: Planning the action, implementing, observing, and reflecting the action. The research was conducted in SMP Negeri 2 located in the cities of Kolaka, Southeast Sulawesi. The data of the study were obtained from the result of observation sheet and from the grammar test, which were taken during the implementation of the action. The data have been analyzed descriptively after collection. Two kinds of data were obtained, namely qualitative and quantitative data. At the end of cycle (post-test) quantity data were obtained from the tests. Qualitative data were taken from observation sheets and surveys conducted during the treatment cycle. The researchers found in the preliminary study that the grammar achievement of the students was low. The researcher applied two cycles, in the first cycle showed that 62.5 % students got the average value above 70, while 37.5 % students got the average value below 70. Minimum completeness criteria in this subject were 75% students got 70 or more. While in the second cycle, the results of the research in cycle II were 83 % students got the average value above 70, while 17 % students got the average value below 70. The results of the research concluded that, the implementation of scramble game in teaching grammar could improve the students’ achievement.